COMPANY GROWTH, ENVIRONMENTAL SOCIAL GOVERNANCE (ESG), GOOD CORPORATE GOVERNANCE, AND FIRM PERFORMANCE: THE ROLE OF CAPITAL STRUCTURE AS A MODERATING VARIABLE - Azet Syam Noor; Luk Luk Fuadah; Yulia Saftiana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the effect of company growth, Environmental Social Governance (ESG), and Good Corporate Governance (GCG) on firm performance with capital structure as a moderating variable in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2012–2023 period. This research employs a quantitative approach using secondary data in the form of annual financial reports collected through documentation techniques. The population consists of 24 SOEs, and total sampling is applied. The analytical methods used are multiple linear regression and Moderated Regression Analysis (MRA) to examine both direct and interaction effects among variables. The variables include company growth, Environmental Social Governance (ESG), Good Corporate Governance (GCG), capital structure (Debt to Equity Ratio/DER), and firm performance measured by Return on Assets (ROA). The results indicate that company growth, ESG, and GCG have a positive and significant effect on firm performance. Capital structure strengthens the positive relationship between company growth and firm performance but does not moderate the relationship between ESG and firm performance. Furthermore, GCG also strengthens the positive relationship between company growth and firm performance.